RADEC Sebagai Inovasi Model Pembelajaran Pendidikan Agama Islam Pasca Pandemi Covid-19 Di Sekolah - Cut Nurhasanah Salsabila Iwanda; Hanifah Nuh Malika; Muhammad Aqshadigrama (Peneliti.net, 2022)
The Covid-19 pandemic has impact to all aspects of human life, including in the world of education. Although the situation is starting back to normal again, the policy of the face-to-face or conventional learning with a learning model same as before the pandemic happened, it can no longer be implemented. It is because the policy of distance learning during the pandemic era made each students at the elementary school level have a difference in model teaching culture and it is created with their respective learning models. Thus, by using the RADEC learning model, it is hoped that it can accommodate the diversity of students interests in learning, especially in Islamic Religious Education. So that teachers can teach (transfer of knowledge) to students can be effective. This research is used a literature study method, which is from book sources and scientific journals related to the topic about the implementation of the RADEC learning model to Islamic Religious Education. There are five syntaxes or steps that need to be considered by the teachers in planning and learning using the RADEC model, namely Read, Answer, Discuss, Explain, and Create. With the RADEC model, students can communicate with other students to equalize perceptions, so that critical thinking skills of the students can be arise.